PENDEKATAN PEMBERDAYAAN MASYARAKAT DALAM PEMBANGUNAN EKONOMI: STUDI KASUS UMKM DESA KADAKAJAYA - Arifin, Farid; Hastika , Nunung; Wulandari, Rafih Sri (STISIP Widyapuri Mandiri Sukabumi, 2025)
This research is motivated by the limited innovation of Patchouli Leaf MSME (Micro, Small and Medium Enterprises) craftsmen in Kadakajaya Village, where MSME craftsmen do not know more about the benefits of Patchouli Leaf for MSME actors, so that from this background the researcher identifies how to effectively increase the productivity of Patchouli Leaf MSME activists in Kadakajaya Village in innovating MSME products. This research uses a qualitative descriptive research design, where research data is obtained through data collection techniques in the form of interviews, observations and documentation studies, data analysis techniques using descriptive techniques including data collection, data condensation, data presentation and conclusion drawing. The results of the study resulted in analyses related to MSME empowerment in terms of awareness, transformation or product innovation and capacity building.